2019
DOI: 10.1088/1361-6463/ab31cb
|View full text |Cite
|
Sign up to set email alerts
|

Regulating phase change behavior and surface characteristics of Sn15Sb85 thin film by oxygen doping

Abstract: In this paper, oxygen doped Sn 15 Sb 85 thin films were proposed to reduce the power consumption for phase change memory (PCM) application. Compared with Sn 15 Sb 85 , oxygen doped Sn 15 Sb 85 thin film had higher crystallization temperature (168 °C-255 °C) and broader energy band gap (1.23-1.55 eV). X-ray diffraction patterns and transmission electron microscope showed that the crystallization of thin film was suppressed and grains became smaller when oxygen was added. After oxygen doping, the surface roughne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Moreover, the O atom has a high electronegativity (3.44), which is easy to combine with the Sb atom that has a low electronegativity (2.05) to form Sb 2 O 3 . 12 It was found that the formation of the Sb In this work, we actually found no formation of the Sb−O bond and that no Sb 2 O 3 phase is separated out in the Sb-GeO 2 (SGO) films. Moreover, together with the flash differential scanning calorimetry (FDSC) method and generalized Mauro−Yue−Ellison−Gupta−Allan (g-MYEGA) viscosity model, we studied the crystallization kinetics features of SGO supercooled liquids and found a distinct fragile-to-strong crossover (FSC) behavior, which benefits to balance the contradiction between the fast crystallization speed around the melting temperature and good thermal stability near the glasstransition temperature.…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…Moreover, the O atom has a high electronegativity (3.44), which is easy to combine with the Sb atom that has a low electronegativity (2.05) to form Sb 2 O 3 . 12 It was found that the formation of the Sb In this work, we actually found no formation of the Sb−O bond and that no Sb 2 O 3 phase is separated out in the Sb-GeO 2 (SGO) films. Moreover, together with the flash differential scanning calorimetry (FDSC) method and generalized Mauro−Yue−Ellison−Gupta−Allan (g-MYEGA) viscosity model, we studied the crystallization kinetics features of SGO supercooled liquids and found a distinct fragile-to-strong crossover (FSC) behavior, which benefits to balance the contradiction between the fast crystallization speed around the melting temperature and good thermal stability near the glasstransition temperature.…”
Section: Introductionmentioning
confidence: 55%
“…In the past decade, many studies focus on the thermal stability of PCMs by introducing gas elements, such as oxygen and nitrogen. Especially, the oxygen-doped Sb-based alloys, such as O 2 -doped Ge-Sb-Te, Ge-Sb, , Sn-Sb, , Zn-Sb, and Si-Sb, have exhibited an improvement in thermal stabilities. However, the excess O 2 doping would bring the negative effects in the phase-change performance, such as the low phase-transition speed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The T c of [Ge(5 nm)/Sb(5 nm)] 5 multilayer films is as high as 203 °C, which demonstrates that the addition of Ge layers has been found to enhance the thermal stability of the films. In addition, as the Ge layer thickness increases, the crystalline resistance of the film increases from 263 Ω of the single-layer Sb film to 1408 Ω of the [Ge(5 nm)/Sb(5 nm)] 5 multilayer film, which can contribute to reducing the drive current of the PCM device during the reset operation 36 .…”
Section: Resultsmentioning
confidence: 99%
“…There are many attractive features of PCRAM such as high density, high access speed, low power consumption and compatibility with CMOS. [1][2][3][4][5] The data storage capability of PCRAM is based on the phase change material transition between crystalline state (low resistance, set state, data 1) and amorphous state (high resistance, reset state, data 0).…”
mentioning
confidence: 99%